A colorblind Christian country?: How racial attitudes affect support for Christian nationalism and civil religion - Walker, Brooklyn (Politics and religion, 2024)
Can racial primes influence support for public expressions of religion? While a growing body of research demonstrates correlations between racial attitudes and support for public religion among White Americans, experimental tests of subconscious connections between the two concepts have been lacking. We utilize a novel survey experiment to prime racial considerations, and we find that Black racial primes raise support for Christian nationalism and civil religion among White Americans, compared to White racial primes. Moreover, our analysis indicates that these effects are attributable to racial animus, namely the evaluation that Black Americans are not prototypical members of the national community. The findings suggest that the preference for a Christian/religious America and a White America are subconsciously interwoven for many White Americans, providing the first experimental evidence, to our knowledge, of this relationship.